PENGARUH KONFLIK BONDHOLDERS-SHAREHOLDERS, BONUS PLAN, DAN UKURAN PERUSAHAAN TERHADAP KONSERVATISME AKUNTANSI (STUDI PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI TERDAFTAR DI BEI PERIODE 2013-2017) - Sarwenda Biduri; Eva Wany; Ade Irma Suryani; Siti Nur Afifah (Lembaga Penelitian Universitas Trisakti, 2019)
This study aims to analyze the effect of bondholder-shareholder conflict,bonus plan and firm size on accounting conservatism in the consumer goodsindustry companies on the IDX for the period of 2013-2017. This researchuses quantitative. The population in this study were 38 consumer goodsindustry companies. The sampling technique in this study used purposivesampling, so that a total sample are 35 observations were obtained consistingof 7 companies for 5 years (2013-2017). The method of data analysis used ismultiple linear regression which is processed in the SPSS application. Theresults of the study show that the conflict of bondholder-shareholders effect onaccounting conservatism, while the bonus plan and firm size have no effect onconservatism of accounting. The results of the research simultaneously showthat the bondholder-shareholder conflict, bonus plan and firm size effect onaccounting conservatism.